The Effectiveness of Community-Based Nutrition Education in Reducing Stunting in Remote Areas: A Systematic Review (Journal of Islamic Nursing, 2026)
Abstract Community-based nutrition education is a key strategy for addressing stunting in geographically isolated regions, yet synthesized evidence on its effectiveness in these specific high-constraint environments remains limited. This systematic review evaluates the impact of community-based nutrition education on stunting and child nutrition outcomes in remote and rural areas. We searched six major databases (ProQuest, ScienceDirect, Scopus, SAGE, SpringerLink, Taylor & Francis) for randomized controlled trials and quasi-experimental studies published between 2014 and 2024. Following PRISMA guidelines, twelve studies (N=53,570) from Asia, Africa, and Latin America were included for qualitative synthesis. Interventions combining nutrition counseling, cooking demonstrations, and home visits significantly improved complementary feeding practices, dietary diversity, and hygiene behaviors. While all studies reported improvements in caregiving, significant reductions in stunting prevalence (ranging from 4.9% to 35%) were primarily observed in multi-year programs that integrated educational components with targeted nutritional supplementation and growth monitoring. In isolation, education improved dietary diversity but had modest, statistically insignificant effects on linear growth. Community-based nutrition education is most effective in reducing stunting when implemented as a multifaceted, long-term intervention linked to social support and supplementation. Policy design for remote areas must prioritize culturally adapted, resource-integrated models to achieve measurable anthropometric gains. Keywords: adolescents, assertive training, boarding school, Islamic values, interpersonal communication.